“BETWEEN THE SACRED AND THE HORRIFIC: AN ANTHROPOLOGICAL READING OF THE FILM MIDSOMMAR” (REMUNOM, 2025)
This article analyzes Ari Aster’s Midsommar (2019) through the lens of symbolic anthropology, investigating how the rituals of the fictional Swedish community Hårga engage with concepts such as myth, totemism, and social cohesion. The central aim is to interpret the group’s cultural practices in light of classical anthropological and psychoanalytic theories, particularly the works of Claude Lévi-Strauss, Émile Durkheim, Sigmund Freud, and Clifford Geertz. The methodology adopted is qualitative film analysis with a hermeneutic approach, treating cinema as a symbolic text. The study highlights rituals both as enactments of foundational myths and as mechanisms of collective organization. The protagonist Dani’s trajectory is read as a rite of passage that transforms her from an emotionally unstable outsider into an integrated central figure within the community. The analysis concludes that Midsommar dramatizes, both visually and narratively, symbolic structures that underpin not only archaic societies but also contemporary forms of belonging. The film demonstrates how cinematic art can represent and question cultural values, challenging boundaries between rationality and affect, tradition and modernity. Ultimately, the study reveals the potential of cinema to visually illustrate anthropological concepts, expanding the scope of anthropological reflection beyond conventional ethnographies.